UPAYA MENINGKATKAN KEMAMPUAN MEMBILANG MELALUI BERMAIN LOTTO ANGKA PADA ANAK KELOMPOK B TK DHARMA WANITA ROWO - Haryanti, Tri (Widya Wacana: Jurnal Ilmiah, 2019)
Ability to say children is the ability of children to count by calling one by one to determine the number or number of objects. Lotto is an educational game used in learning activities in children. The use of lottery media numbers is a form of recognizing numbers in early childhood. The rationale for the emergence of this problem is still the low ability to say children of the Rowo B TK Dharma Wanita Group. The purpose of this study is 1) to find out how to play lotto numbers that can improve the ability to say, children, 2) to understand the ability to remember the ability to count children through playing lotto numbers in children B TK Dharma Wanita Rowo Kandangan Group Semester II 2017/2018 Academic Year. The subjects of this study were students of the Group B TK Dharma Wanita Rowo donated by 25 children. The research was conducted in February 2018. Data collection methods used were observation, documentation, and interviews. Based on the results of the research and discussion, it can be concluded that through the lotto numbers game can improve the ability to count children in the TK B Group of Dharma Wanita Rowo Kandangan Temanggung Semester II 2017/2018 Academic Year. This is evidenced by the increase. The increase only reached 20%, then after the increase in Cycle I it increased to 52%, and Cycle II to 84%, has reached 80%. This success is marked by the child being able to lift by pointing objects, connecting / pairing symbols with objects and writing numbers..Â Key words: Ability To Say, Lotto NumbersÂ